DRIVERS OF INTENTIONS TO PURCHASE SHRIMP PRODUCTS IN SWITZERLAND - Saesoo, Suthasinee (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The drivers of intention to purchase towards local shrimps products in Switzerland was conducted to examine the relationship between variables; attitude towards local shrimp consumption, attitude towards supporting local agri-business, consumer ethnocentrism, subjective norms, and intention to purchase. In this study, the Theory of Reasoned Action (TRA) was applied. One hundred respondents were asked to complete the questionnaire. Then, the process of analyzing the data was taken. All six hypotheses were tested by Pearson Correlation method and found that all hypotheses were supported. The strongest factor was found to be subjective norms on attitudes towards consuming local shrimp products. The consumers that have been positively influenced by people are more likely to have a good attitude about the products, which leads to the decision to purchase the products in the future. In addition, the positive attitude towards consuming local shrimp products is supported by an attitude towards supporting local agribusiness, ethnocentric tendencies, and subjective norms. Therefore, the research also gave some useful suggestions for those who interested in.